Socio-Engineering Intervention in Child Health: Bridging Society and Technology - Kumar, Roopak; Barthwal, Pradeep Kumar; Paliwal, Vijay; Khanduri, Atul; Joshi, Neelam; Kalsan, Priya (Journal of Neonatal Surgery, 2025)
Child health is influenced by a complex interplay of social, environmental, and technological factors. This research explores child well-being through a multidisciplinary framework that integrates sociology with mechanical, civil, electrical & electronics engineering to develop holistic health interventions. From a sociological perspective, the study examines how family structures, community engagement, education, and socioeconomic conditions impact health outcomes in children. Mechanical engineering contributes through the design of ergonomic medical devices and pediatric health tools tailored to the physical needs of children. Civil engineering plays a role in developing child-friendly infrastructure, such as safe housing, hygienic sanitation systems, and accessible healthcare facilities, which form the backbone of a healthy living environment. Electrical & Electronics engineering supports the integration of monitoring systems, wearable health technologies, and remote care networks that enable early detection and continuous care. Together, these disciplines form a cohesive strategy that not only addresses the immediate medical needs of children but also promotes long-term well-being through sustainable, socially-informed engineering solutions. The study underscores the importance of interprofessional collaboration in creating inclusive health systems that respond to both physical and social determinants of child health.